Egg size Variation in the Collared Flycatcher (Ficedula albicollis Temminck, 1815) - Atemasova, T.; Devyatko, T.; Atemasov, A. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2025)
This work aims to examine the factors influencing variation of the Collared Flycatcher’s egg size at the southern borders of the distribution of deciduous forests (Homil’shanski Lisy National Park, Ukraine). In total, data on 298 clutches and 1971 eggs of the Collared Flycatcher in artificial nest-boxes for 2006‒2011 and 2013‒2021 were used for analyses. As the meteorological indicators we used the temperature, a number of days with rainfall during the 1st decade of May; and humidity indices. All statistical analyses were performed with R statistical software version 4.4.2, A Shapiro–Wilk test for normality revealed that data were not normally distributed. Therefore, for further analysis, we used the Kruskal – Wallis test and Dunn test as well as Permutational Analysis of Variance (PERMANOVA) of the distance matrix. The vegan package was used for analysis. We analyzed the effects of meteorological indicators on egg size using generalized additive models. Statistical analyses were performed using mgcv packages.In the studied subpopulation, the average egg length tends to decrease in the period from 2006 to 2021 and is slightly dependent on clutch size and the decade of first-egg laying. The seasons with the smallest egg sizes in the studied subpopulation spanned 2014 - 2018; later on, there was an increase in egg diameter towards the usual size for this subpopulation. The consistently small diameter of the eggs can be assumed to indicate that during this period, young females predominated in the studied subpopulation.In general, the size of the eggs in the last season was similar and even somewhat larger (especially in length) to those obtained in the Sumy region of Ukraine, and in certain years exceeded the indicators of the eggs of flycatchers from the Bialowieza Forest. It can be assumed that larger eggs are laid by females under optimal conditions within the species’ range; as they move towards the borders of the range to the north and east, the morphometric parameters may decrease due to the decline in the quality (abundance of food) of the environment.The analysis of the repeatability of egg sizes in the same female should answer the question of whether the size of the egg is an individual’s characteristics of females. However, we did not receive a definitive answer.The humidity of the pre-laying decade has a significant negative impact on the morphological parameters. The humidity during the egg-laying decade has a positive influence, while to a lesser extent, the temperature of the decade prior to egg-laying also positively affects the length of the eggs. The temperature of the previous decade and the number of rainy days play a minor role. At the same time, there is an optimum for these indicators, beyond which the effect of their influence on the size of the eggs changes to the opposite. In the studied area, the length and diameter of eggs from early and late did not differ significantly. Only in certain years, the differences in length, diameter, and volume are significant.The variation of the morphological parameters are an integrated response to the instability of environmental parameters. One of the reasons for high variability in egg sizes may be humidity. The size of the eggs itself cannot be explained by the climatic conditions of the current year. They are an integrated indicator of the female's maturity and the nutritional conditions of the season.